Aleksota by Seweryna Pruszakowa and Stanisław Moniuszko – a rediscovered link? - Dziadek, Magdalena; Okulicz-Kozaryn, Radosław (Chopin Review, 2025)
Held among the Moniuszko papers in the Warsaw Music Society archives is the libretto to the planned – but ultimately not written – opera Aleksota, penned by Seweryna Pruszakowa, which since 2023 has also been available in digital form on the website Polish Music Heritage in Open Access. It combines motifs taken from romantic Lithuanian mythology with fictional episodes from the history of the country’s Christianisation. The libretto was discussed and analysed by Włodzimierz Poźniak, but since he published the results of his research (1948), crucial new questions have arisen, which the authors of this article attempt to answer. They concern above all the origins of Moniuszko’s idea for a ‘Lithuanian opera’ and specific circumstances behind the project. They seem to be directly linked to the wave of patriotic, democratic and solidarity demonstrations which – having swept the lands of the former Commonwealth of Poland–Lithuania over the course of the year 1861 – on 12 August reached Kaunas and nearby Aleksota and came together on a bridge over the river Niemen. The authors go on to indicate the literary sources for the libretto, and especially a work by Aleksander Połujański which they came across, attempting to answer the question as to the musical concept behind the opera, which Moniuszko elaborated with Pruszakowa before the outbreak of the January Uprising and her subsequent departure for Paris.